2019
DOI: 10.1111/aas.13324
|View full text |Cite
|
Sign up to set email alerts
|

Post‐extubation continuous positive airway pressure improves oxygenation after pediatric laparoscopic surgery: A randomized controlled trial

Abstract: Background: Effects of intraoperative recruitment maneuvers (RMs) on oxygenation and pulmonary compliance are lost during recovery if high inspired oxygen and airway suctioning are used. We investigated the effect of post-extubation noninvasive CPAP mask application on the alveolar arterial oxygen difference [(A-a) DO 2 ] after pediatric laparoscopic surgery. Methods: Sixty patients (1-6 years) were randomly allocated to three groups of 20 patients, to receive zero end-expiratory pressure (ZEEP group), RM with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
4
0
2
Order By: Relevance
“…Insbesondere bei Kindern mit chronischen Atemwegs-und Lungenerkrankungen, angeborenen Herzfehlern oder mit neuromuskulären Erkrankungen kann nach großen Operationen, wie z. B. Wirbelsäulenoperationen, NIV hilfreich sein [506,560,561,598]. Bei Letzteren speziell ist die NIV am besten präoperativ zu beginnen, um perioperative Komplikationen zu vermeiden [598].…”
Section: Asthmaunclassified
“…Insbesondere bei Kindern mit chronischen Atemwegs-und Lungenerkrankungen, angeborenen Herzfehlern oder mit neuromuskulären Erkrankungen kann nach großen Operationen, wie z. B. Wirbelsäulenoperationen, NIV hilfreich sein [506,560,561,598]. Bei Letzteren speziell ist die NIV am besten präoperativ zu beginnen, um perioperative Komplikationen zu vermeiden [598].…”
Section: Asthmaunclassified
“…Ambrosio et al observed decrease in P(A-a)O 2 with increasing PEEP from 5 -20 cmH 2 O (4). In pediatric patients, titration of PEEP decreased P(A-a)O 2 1 hour after laparscopic surgery compered to children ventilated without PEEP (17). Positive pressure ventilation with PEEP 10 cmH 2 O also caused a Results are presented as mean and CI 95%.…”
Section: Discussionmentioning
confidence: 99%
“…After the screening process, 18 of the 4,267 identified studies were considered potential candidates for inclusion in the systematic review. 7,10,11,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Five studies were excluded because they were surveys on extubation techniques or airway management. 10,11,[19][20][21] In addition, 6 studies were excluded because they did not compare positive-pressure and suctioning techniques.…”
Section: Study Selectionmentioning
confidence: 99%
“…10,11,[19][20][21] In addition, 6 studies were excluded because they did not compare positive-pressure and suctioning techniques. [22][23][24][25][26][27] A total of 7 studies, 6 RCTs 7,28-32 and 1 non-randomized controlled study, 33 were finally included in the systematic review.…”
Section: Study Selectionmentioning
confidence: 99%